Inhibition of group IVA cytosolic phospholipase A2 by thiazolyl ketones in vitro, ex vivo, and in vivo - Kokotos, G.; Feuerherm, A. J.; Barbayianni, E.; Shah, I.; Saether, M.; Magrioti, V.; Nguyen, T.; Constantinou-Kokotou, V.; Dennis, E. A.; Johansen, B. (Journal of Medicinal Chemistry, 2014)
Group IVA cytosolic phospholipase A2 (GIVA cPLA2) is the rate-limiting provider of pro-inflammatory mediators in many tissues and is thus an attractive target for the development of novel anti-inflammatory agents. In this work, we present the synthesis of new thiazolyl ketones and the study of their activities in vitro, in cells, and in vivo. Within this series of compounds, methyl 2-(2-(4-octylphenoxy)acetyl)thiazole-4-carboxylate (GK470) was found to be the most potent inhibitor of GIVA cPLA2, exhibiting an XI(50) value of 0.011 mole fraction in a mixed micelle assay and an IC50 of 300 nM in a vesicle assay. In a cellular assay using SW982 fibroblast-like synoviocytes, it suppressed the release of arachidonic acid with an IC50 value of 0.6 μM. In a prophylactic collagen-induced arthritis model, it exhibited an anti-inflammatory effect comparable to the reference drug methotrexate, whereas in a therapeutic model, it showed results comparable to those of the reference drug Enbrel. In both models, it significantly reduced plasma PGE2 levels.
Keywords: Animals; Arachidonic Acid/secretion; Arthritis/blood/chemically induced/drug therapy; Blood Proteins/chemical synthesis/*chemistry/*pharmacology/therapeutic use; Cell Line, Tumor; Collagen/adverse effects; Cytosol/*enzymology; Dinoprostone/blood; drug design; Group IV Phospholipases A2/*antagonists & inhibitors; Humans; Ketones/*chemistry; Male; Mice; Oleic Acid/secretion; Synovial Membrane/drug effects/metabolism/secretion; Thiazoles/chemical synthesis/*chemistry/*pharmacology/therapeutic use